Late Cenozoic co-evolution of tectonics, weathering, and climate in the Amazon Basin : Insights from neodymium and hafnium isotopes - Moizinho, Gabriel Ribeiro (2025)
Tese (doutorado) — Universidade de Brasília, Instituto de Geociências, Programa de Pós-Graduação em Geologia, 2025.